Rectifying inaccuracies in adsorption modeling. Comment on ?amino- and sulfur-containing POSS for highly efficient and selective extraction of platinum group elements from acidic solution? - Chu K.H.; Hashim M.A.; Hayder G.; Bollinger J.-C. (Elsevier Ltd, 2025)
In this critique, we address multiple shortcomings identified in a recent article published in this journal concerning the adsorption of Pd(II) and Pt(IV) ions from acidic solutions using a novel nanoadsorbent. The identified issues encompass erroneous model equations, unverified adsorption mechanisms, inappropriate application of simplified models, incorrect parameter units, and flawed thermodynamic parameters. ? 2024 Elsevier Ltd